Severe Illness Anxiety Treated by Integrating Inpatient Psychotherapy With Medical Care and Minimizing Reassurance - Higgins-Chen, Albert T.; Abdallah, Sarah B.; Dwyer, Jennifer B.; Kaye, Alfred P.; Angarita, Gustavo A.; Bloch, Michael H. (Frontiers in Psychiatry, 2019)
Illness anxiety disorder (IAD, formerly hypochondriasis) is characterized by preoccupation with fear of serious illness despite medical reassurance. IAD is common, debilitating, challenging to treat, and results in high healthcare utilization. Outpatient management of IAD is challenging because patients can compulsively seek reassurance from numerous providers, which interferes with learning more productive coping skills. We present the case of a woman with severe IAD who presented to the emergency room with increasing frequency over several months, despite regular outpatient medical visits and escalating psychiatric care. We made the unusual decision to hospitalize her for IAD for one month, in the absence of typical hospitalization criteria. This hospitalization allowed us to consolidate all medical and psychiatric care into a single provider team and train all staff and family to communicate with her in a consistent manner. We successfully treated her by integrating a general cognitive-behavioral therapy (CBT) protocol into medical care and decision-making. In response to her numerous health concerns, we minimized medical work-up, reassurance and reactive medication changes, and instead used the concerns as opportunities to reinforce the psychotherapy. This approach allowed us to simplify her medication regimen and manage her co-morbid hypertension and vitamin deficiencies. Though inpatient hospitalization is likely infeasible in most cases of IAD, outpatient providers may create similar treatment plans based on the example of our case report, without needing highly specialized expertise. Such a plan would require a straightforward understanding of IAD psychology, which we review here, combined with readily accessible tools including a universal CBT protocol, online CBT courses, and clinical symptom scales. We discuss our approach for responding to health concerns, maintaining therapeutic alliance, integrating CBT principles into patient interactions, and managing medications. Since patients with IAD share health concerns with all providers, staff, and family, we also include our own IAD communication guide, appropriate for a general audience, that demonstrates how to respond in these conversations.